FROM GLOBAL TO LOCAL: FEASIBILITY OF THE INDICATOR ANALYSIS OF THE SUSTAINABLE DEVELOPMENT IN UKRAINE - Kiptenko V. K. (World Science, 2019)
Responding to the global concern on sustainable development, the consistency of localized and global/regional practices impacts the public and civil, economic, social and cultural domains. Challenges of coherent and efficient monitoring system mark the Ukraine’s path and leave space for improvement. The scrutiny of academic and institutional efforts in monitoring the sustainable development, sustainable development goals implementation reveals shortcomings and pitfalls in metadata provision, tools for data collection and processing, congruence of understanding and interpreting the concepts. The outcomes serve to substantiation of the research and educational objectives for examination of the indicator analysis design for better policy- and decision-making, public awareness, spatial patterns representation.